Extreme weather exacerbates ozone pollution in the Pearl River Delta, China: role of natural processes - N. Wang; H. Wang; X. Huang; X. Chen; Y. Zou; T. Deng; T. Li; X. Lyu; F. Yang (Atmospheric Chemistry and Physics, 2024)
Ozone (O3) pollution research and management in China have mainly focused on anthropogenic emissions, while the importance of natural processes is often overlooked. With the increasing frequency of extreme weather events, the role of natural processes in exacerbating O3 pollution is gaining attention. In September 2022, the Pearl River Delta (PRD) in southern China experienced an extended period (25 d) of regional O3 exceedances and high temperatures (second highest over last 2 decades) due to extreme weather conditions influenced by the subtropical high and typhoon peripheries. Employing an integrated approach involving field measurements, machine learning and numerical model simulations, we investigated the impact of weather-induced natural processes on O3 pollution by considering meteorological factors, natural emissions, chemistry pathways and atmospheric transport. The hot weather intensified the emission of biogenic volatile organic compounds (BVOCs) by ∼10 %. Isoprene and biogenic formaldehyde accounted for 47 % of the in situ O3 production, underscoring the predominant role of BVOC emissions in natural processes. The chemical pathway of isoprene contributing to O3 formation was further explored, with O3 production more attributable to the further degradation of early generation isoprene oxidation products (contributed 64.5 %) than the direct isoprene oxidation itself (contributed 35.5 %). Besides, it was found that the hot weather significantly promoted regional photochemical reactions, with meteorological factors contributing to an additional 10.8 ppb of O3 levels compared to normal conditions. Temperature was identified as the dominant meteorological factor. Furthermore, the typhoon nearing landfall significantly enhanced the cross-regional transport of O3 from northern to southern China through stratosphere–troposphere exchange (STE). The CAM-Chem model simulations revealed that the STE-induced O3 on the PRD surface could reach a maximum of ∼8 ppb, highlighting the non-negligible impact of STE. This study highlights the importance of natural processes exacerbated by extreme weather events in O3 pollution and provides valuable insights into O3 pollution control under global warming.